"The Nestornaut", or how a president becomes a comic superhero - Palacios, Cristian (2020)
Published for the first time in 1957, The Eternaut, created by Hector German Oesterheld and drawn by Francisco Solano Lopez, became with the pass of the years not just a classic comic, but also an authentic milestone in all the Argentinian culture. Read as a political allegory of the fight against the successive military dictatorships in what we considered an enormous misunderstood motivated, that's true, by Oesterheld's personal history, "disappeared" and murdered together with his four daughters; this first Eternaut was employed as a symbol by intellectuals and political movements after the return of democracy in the country. One of the latest deviations of the Eternaut as a politic symbol is the Nestornaut, that is, a picture of the Peronist president Nestor Kirchner wearing the Eternaut's typical homemade diving suit. The success of this particular image turn out to be colossal after the president's decease in October 2010 and was used during his funeral and, after that, on t-shirts, stencils, murals and as a banner in civic events like the criminal trials of the last dictatorship repressors. In this work we attempt to understand the conditions of possibility of the success of this particular image in which we consider it is possible to find the confluence of many complex factors including the political history of the Peronism, the status of the comic Art in modern Argentinian society, its historic role as a catalyst for the violence in the sixties and seventies and the life after page of certain comic book characters.